2012
DOI: 10.3109/02656736.2011.644621
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and volume effects in thermochemical ablation in vivo: Results in a porcine model

Abstract: The method can be used successfully to ablate tissue in vivo. By neutralising acid in situ and releasing heat and a salt, this technique improves considerably upon the use of acetic acid used alone. Peak temperatures exceeded accepted coagulation thresholds even if the only mechanism operating was hyperthermia. Reagent concentrations and volumes increased the amount of the coagulum but not in a linear fashion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…1 However, for larger tumors >5 cm in diameter, studies have reported lower complete ablation rates, 24% and 62% in tumors measuring 5-9.5 cm and 5-7 cm. 8 Similar results have been reported with early MW ablations systems. Suggested reasons for recurrence due to inadequate ablation include limitations of the heat-sink effect associated with large blood vessels, imprecise placement of applicators during sequential ablations resulting in nonoverlapping ablation zones, limitations of the heating technology, and poor visualization of the treatment zone on preoperative and postoperative imaging.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…1 However, for larger tumors >5 cm in diameter, studies have reported lower complete ablation rates, 24% and 62% in tumors measuring 5-9.5 cm and 5-7 cm. 8 Similar results have been reported with early MW ablations systems. Suggested reasons for recurrence due to inadequate ablation include limitations of the heat-sink effect associated with large blood vessels, imprecise placement of applicators during sequential ablations resulting in nonoverlapping ablation zones, limitations of the heating technology, and poor visualization of the treatment zone on preoperative and postoperative imaging.…”
Section: Introductionsupporting
confidence: 80%
“…Since ultrasound energy from interstitial applicators is tightly collimated to the individual transducers along the length of the applicator, 16 it offers the potential to avoid skin burns and unpredictable energy deposition patterns, especially when heating tumors closer to the surface of the liver. It should be noted that this collimation and high operating frequency (6)(7)(8) precludes the possibility of using phasing strategies between applicators for focusing energy, which is possible with MW applicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used energy sources include radio frequency, microwaves, lasers, and cryoablation. 1,2 Thermochemical ablation 3 and irreversible electroporation 4 have recently emerged as other modalities for tissue ablation. High intensity focused ultrasound offers the potential for image-guided noninvasive treatment of deep targets.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the heat transfer for such applications usually involves one or more of the following methods: direct in vivo temperature measurement [1,2], numerical modeling [3][4][5], and in vitro modeling using tissue phantoms [6][7][8][9]. In vivo measurements have obvious availability issues and can explore only a limited region of parameter space, while some scenarios require additional coupled processes that are not accurately incorporated computationally (e.g., bacterial cultures).…”
Section: Introductionmentioning
confidence: 99%